POTENSI NITRIFIKASI OLEH BAKTERI PADA DAERAH MUARA SUNGAI studi kasus : Muara Sungai Plumbon, Banjir Kanal Barat, Banjir Kanal Timur – Semarang - Kartika Hapsari (Jurnal Teknik Lingkungan, 2012)
The estuary is the area of coexistence between sea water and fresh water so estuary have a fairly high levels of salinity. Most industries such as fish canning industry, leather industry, petrolum industry and a population of about disposing discharge in river watersheed giving rise to pollution, including nitrogen levels are high in the River. High concentrations of N and exceeding the threshold causes eutrophication.Stage N compounds in water in salinity by means of nitrification bacteria that have been tolerant landscaping needs. Between estuary in the River Plumbon, River Banjir Kanal Barat and Banjir Kanal Timur of nitrogen during the process speed allowance nitrification most optimal on the estuary Banjir Kanal Timur, because nitrification bacteria in the mouth of the river has been in the process of nitrification tolerant than both estuary other.